Wear-resistant refractory brick and preparation method thereof
By using specific combinations of raw materials and processes in refractory bricks, including molybdenum disulfide, low-carbon ferromanganese and modified carbon nanotubes, the problem of insufficient wear resistance of refractory bricks is solved, significantly improving wear resistance and extending service life.
Patent Information
- Application Number
- CN202411861876.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
The wear resistance of existing refractory bricks is insufficient and it is difficult to meet the strict working conditions in high-temperature industrial scenarios.
A wear-resistant refractory brick is used, and its raw materials include graphene, silicon carbide, mullite, high alumina bauxite, aluminum powder, molybdenum disulfide, low-carbon ferromanganese and modified carbon nanotubes. The wear resistance of the brick is improved through specific calcining, pressure forming and firing processes.
Through the synergy between molybdenum disulfide and low-carbon ferromanganese and the modification of carbon nanotubes by nanoalumina and nanomagnesium oxide, the wear resistance of wear-resistant refractory bricks is significantly improved and its service life in industrial scenarios is extended.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wear-resistant refractory materials, and in particular to a wear-resistant refractory brick and a preparation method thereof. Background Art
[0002] In the process of vigorous development of modern industry, many harsh working conditions have posed unprecedented challenges to material performance. Against this background, wear-resistant refractory bricks came into being and quickly became an indispensable key material in many high-temperature industrial scenarios.
[0003] In the hot process of steel smelting, there is molten iron and slag inside the blast furnace, which puts more stringent requirements on the wear resistance of the refractory bricks lining the furnace wall; in the glass melting furnace, the molten glass is viscous. During the stirring and flowing process, the refractory bricks ensure the purity of the glass liquid and the continuous and stable operation of the production line with their excellent wear resistance. It can be seen that the wear resistance of refractory bricks plays a vital role in extending their service life in industrial scenarios.
[0004] In order to meet the growing industrial demand, scientific researchers have continuously innovated and developed a variety of wear-resistant refractory bricks. However, despite many advances, the wear resistance of refractory bricks still needs to be further improved. Summary of the invention
[0005] The invention provides a wear-resistant refractory brick and a preparation method thereof, which solves the problem of poor wear resistance of refractory bricks in the related art.
[0006] The technical solution of the present invention is as follows: The present invention provides a wear-resistant refractory brick, wherein the raw materials include the following components by weight: 5-10 parts of graphene, 5-10 parts of silicon carbide, 5-15 parts of mullite, 15-30 parts of high-alumina bauxite, 5-10 parts of aluminum powder, 5-12 parts of molybdenum disulfide, 1-10 parts of low-carbon ferromanganese, and 5-10 parts of modified carbon nanotubes; The raw materials for modifying the carbon nanotubes include the following components by weight: 1 to 3 parts of nano-aluminum oxide, 2 parts of nano-magnesium oxide and 50 parts of carbon nanotubes.
[0007] As a further technical solution, the mass ratio of molybdenum disulfide to low-carbon ferromanganese is 1~3:1.
[0008] As a further technical solution, the mass ratio of molybdenum disulfide to low-carbon ferromanganese is 2:1.
[0009] As a further technical solution, the method for preparing the modified carbon nanotubes comprises the following steps: A1, placing carbon nanotubes in acid, reacting, filtering, washing, and drying to obtain acid-treated carbon nanotubes; A2, mixing the acid-treated carbon nanotubes with nano-alumina and nano-magnesia, adding ethanol to mix evenly, drying, and modifying to obtain the modified carbon nanotubes.
[0010] As a further technical solution, the mass volume ratio of the carbon nanotubes to the acid in A1 is 1g:50~150mL.
[0011] As a further technical solution, the acid in A1 is a mixture of sulfuric acid and nitric acid.
[0012] As a further technical solution, the volume ratio of the sulfuric acid to the nitric acid is 1:0.5-1.5, the mass concentration of the sulfuric acid is 70%-98%, and the mass concentration of the nitric acid is 65%-80%.
[0013] As a further technical solution, the reaction temperature in A1 is 70-90°C and the reaction time is 0.5-1h.
[0014] As a further technical solution, the drying temperature in A1 is 90-110° C. and the drying time is 10-12 hours.
[0015] As a further technical solution, the mass of ethanol described in A2 is 5% to 15% of the total mass of the acid-treated carbon nanotubes, nano-alumina and nano-magnesium oxide.
[0016] As a further technical solution, the drying temperature in A2 is 90-110° C. and the drying time is 1-3 hours.
[0017] As a further technical solution, the modification temperature in A2 is 600-800°C and the time is 1-3h.
[0018] The present invention also proposes a method for preparing wear-resistant refractory bricks, comprising the following steps: S1, mixing and calcining graphene, silicon carbide and mullite to obtain a first mixed material; S2, mixing the first mixture with high-alumina bauxite, aluminum powder, molybdenum disulfide, low-carbon ferromanganese, and modified carbon nanotubes to obtain a second mixture, and the second mixture is pressure-formed to obtain a brick; S3. After being dried, fired and kept warm, the bricks are cooled to room temperature to obtain wear-resistant refractory bricks.
[0019] As a further technical solution, the calcination temperature in S1 is 540-560° C. and the calcination time is 4-6 hours.
[0020] As a further technical solution, the pressure of the pressure forming in S2 is 900~1300kN.
[0021] As a further technical solution, the drying temperature in S3 is 60-80° C. and the drying time is 1-3 hours.
[0022] As a further technical solution, the sintering described in S3 includes three stages. In the first stage, the temperature is heated from room temperature to 400~600℃, and the insulation time is 2~4h; in the second stage, the temperature continues to be heated to 1000~1200℃, and the insulation time is 2~4h; in the third stage, the temperature continues to be heated to 1500~1700℃, and the insulation time is 8~10h.
[0023] As a further technical solution, the insulation described in S3 includes two stages. In the first stage, the temperature is 250~300℃, and the insulation time is 2~4h; in the second stage, the temperature is cooled to 100~130℃, and the insulation time is 2~4h.
[0024] The working principle and beneficial effects of the present invention are: In the present invention, molybdenum disulfide and low-carbon ferromanganese work synergistically to improve the wear resistance of wear-resistant refractory bricks. Nano-alumina and nano-magnesia are used to modify carbon nanotubes to improve the dispersibility of carbon nanotubes in the matrix, thereby improving the wear resistance of wear-resistant refractory bricks. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the following embodiments and comparative examples, the carbon content of graphene is 99wt%, and the particle size is 2000 mesh, the purity of silicon carbide is 95wt%~98.5wt%, and the particle size is 60~325 mesh, the particle size of mullite is 200 mesh, the alumina content of high alumina bauxite is ≥88wt%, and the particle size is 200 mesh, the aluminum content of aluminum powder is 99.5wt%, and the particle size is 200 mesh, the purity of molybdenum disulfide is 99wt%, and the particle size is 300 mesh, the purity of low-carbon ferromanganese is 99.9wt%, and the particle size is 400 mesh, carbon nanotubes are purchased from Tianjin Jinglin New Materials Technology Co., Ltd., the article number is SG-100, nano alumina is purchased from Hangzhou Wanjing New Materials Co., Ltd., the article number is VK-L20Y, and nano magnesium oxide is purchased from Hangzhou Wanjing New Materials Co., Ltd., the article number is VK-JH05.
[0027] Example 1 A method for preparing a wear-resistant refractory brick comprises the following steps: S1, mixing 10 parts of graphene, 10 parts of silicon carbide, and 15 parts of mullite and calcining them at 540° C. for 6 hours to obtain a first mixture; S2, mixing the first mixture with 30 parts of high-alumina bauxite, 10 parts of aluminum powder, 12 parts of molybdenum disulfide, 10 parts of low-carbon ferromanganese, and 10 parts of modified carbon nanotubes to obtain a second mixture, and the second mixture is formed by a pressure of 1300 kN to obtain a brick; S3, the bricks are dried at 60°C for 3h, fired and kept warm, and then cooled to room temperature to obtain wear-resistant refractory bricks; The raw materials for modifying carbon nanotubes include the following components by weight: 3 parts of nano-alumina, 2 parts of nano-magnesium oxide and 50 parts of carbon nanotubes; The method for preparing modified carbon nanotubes comprises the following steps: A1. Place carbon nanotubes in mixed acid, the mass volume ratio of carbon nanotubes to mixed acid is 1 g:150 mL, the mixed acid is a mixture of sulfuric acid and nitric acid, the volume ratio is 1:1.5, the mass concentration of sulfuric acid is 98%, and the mass concentration of nitric acid is 80%, react at 70°C for 1 hour, filter and wash, and dry at 90°C for 12 hours to obtain acidified carbon nanotubes; A2, mixing the acid-treated carbon nanotubes with nano-alumina and nano-magnesia, adding ethanol to mix evenly, the mass of ethanol being 15% of the total mass of the acid-treated carbon nanotubes, nano-alumina and nano-magnesia, drying at 90°C for 3h, heating at 600°C for modification for 3h, to obtain modified carbon nanotubes; The firing process includes three stages. In the first stage, the temperature is heated from room temperature to 400°C, and the holding time is 4 hours. In the second stage, the temperature is continuously heated to 1000°C, and the holding time is 4 hours. In the third stage, the temperature is continuously heated to 1500°C, and the holding time is 10 hours. The insulation process includes two stages. In the first stage, the temperature is 250°C and the insulation time is 4 hours. In the second stage, the temperature is lowered to 100°C and the insulation time is 4 hours.
[0028] Example 2 A method for preparing a wear-resistant refractory brick comprises the following steps: S1, mixing 5 parts of graphene, 5 parts of silicon carbide, and 5 parts of mullite and calcining them at 560° C. for 4 hours to obtain a first mixture; S2, mixing the first mixture with 15 parts of high-alumina bauxite, 5 parts of aluminum powder, 5 parts of molybdenum disulfide, 1 part of low-carbon ferromanganese, and 5 parts of modified carbon nanotubes to obtain a second mixture, and the second mixture is formed by a pressure of 900 kN to obtain a brick; S3, the bricks are dried at 80°C for 1 hour, fired and kept warm, and then cooled to room temperature to obtain wear-resistant refractory bricks; The raw materials for modifying carbon nanotubes include the following components by weight: 1 part of nano-alumina, 2 parts of nano-magnesium oxide and 50 parts of carbon nanotubes; The method for preparing modified carbon nanotubes comprises the following steps: A1. Place carbon nanotubes in mixed acid, the mass volume ratio of carbon nanotubes to mixed acid is 1 g:50 mL, the mixed acid is a mixture of sulfuric acid and nitric acid, the volume ratio is 1:0.5, the mass concentration of sulfuric acid is 70%, and the mass concentration of nitric acid is 65%, react at 90°C for 0.5h, filter and wash, and dry at 110°C for 10h to obtain acidified carbon nanotubes; A2, mixing the acid-treated carbon nanotubes with nano-alumina and nano-magnesia, adding ethanol to mix evenly, the mass of ethanol being 5% of the total mass of the acid-treated carbon nanotubes, nano-alumina and nano-magnesia, drying at 110°C for 1 hour, and heating at 800°C for 1 hour to obtain modified carbon nanotubes; The firing process includes three stages. In the first stage, the temperature is heated from room temperature to 600°C for 2 hours. In the second stage, the temperature is continuously heated to 1200°C for 2 hours. In the third stage, the temperature is continuously heated to 1700°C for 8 hours. The insulation process includes two stages. In the first stage, the temperature is 300°C and the insulation time is 2 hours. In the second stage, the temperature is lowered to 130°C and the insulation time is 2 hours.
[0029] Example 3 A method for preparing a wear-resistant refractory brick comprises the following steps: S1, mixing 8 parts of graphene, 8 parts of silicon carbide, and 10 parts of mullite and calcining them at 550° C. for 5 hours to obtain a first mixture; S2, mixing the first mixture with 25 parts of high-alumina bauxite, 8 parts of aluminum powder, 10 parts of molybdenum disulfide, 2 parts of low-carbon ferromanganese, and 8 parts of modified carbon nanotubes to obtain a second mixture, and the second mixture is formed by a pressure of 1100 kN to obtain a brick; S3, the bricks are dried at 70°C for 2h, fired and kept warm, and then cooled to room temperature to obtain wear-resistant refractory bricks; The raw materials for modifying carbon nanotubes include the following components by weight: 2 parts of nano-alumina, 2 parts of nano-magnesium oxide and 50 parts of carbon nanotubes; The method for preparing modified carbon nanotubes comprises the following steps: A1. Place carbon nanotubes in mixed acid, the mass volume ratio of carbon nanotubes to mixed acid is 1 g:100 mL, the mixed acid is a mixture of sulfuric acid and nitric acid, the volume ratio is 1:1, the mass concentration of sulfuric acid is 85%, and the mass concentration of nitric acid is 70%, react at 80°C for 0.5 h, filter and wash, and dry at 100°C for 11 h to obtain acidified carbon nanotubes; A2, mixing the acid-treated carbon nanotubes with nano-alumina and nano-magnesia, adding ethanol to mix evenly, the mass of ethanol being 10% of the total mass of the acid-treated carbon nanotubes, nano-alumina and nano-magnesia, drying at 100°C for 2h, and heating at 700°C for 2h to obtain modified carbon nanotubes; The firing process includes three stages. In the first stage, the temperature is heated from room temperature to 500°C for 3 hours. In the second stage, the temperature is continuously heated to 1100°C for 3 hours. In the third stage, the temperature is continuously heated to 1600°C for 9 hours. The insulation process includes two stages. In the first stage, the temperature is 275°C and the insulation time is 3 hours. In the second stage, the temperature is lowered to 120°C and the insulation time is 3 hours.
[0030] Example 4 The only difference between this embodiment and embodiment 3 is that, in this embodiment, the weight portion of molybdenum disulfide is 5 parts and the weight portion of low-carbon ferromanganese is 7 parts.
[0031] Example 5 The only difference between this embodiment and embodiment 3 is that, in this embodiment, the weight portion of molybdenum disulfide is 6 parts and the weight portion of low-carbon ferromanganese is 6 parts.
[0032] Example 6 The only difference between this embodiment and embodiment 3 is that, in this embodiment, the weight parts of molybdenum disulfide are 8 parts, and the weight parts of low-carbon ferromanganese are 4 parts.
[0033] Example 7 The only difference between this embodiment and embodiment 3 is that, in this embodiment, the weight portion of molybdenum disulfide is 9 parts, and the weight portion of low-carbon ferromanganese is 3 parts.
[0034] Comparative Example 1 The only difference between this comparative example and Example 2 is that this comparative example uses 5 parts of carbon nanotubes instead of 5 parts of modified carbon nanotubes.
[0035] Comparative Example 2 The difference between this comparative example and Example 2 is that the raw materials for modifying carbon nanotubes in this comparative example include the following components by weight: 3 parts of nano-alumina and 50 parts of carbon nanotubes; The method for preparing modified carbon nanotubes comprises the following steps: A1. Place carbon nanotubes in mixed acid, the mass volume ratio of carbon nanotubes to mixed acid is 1 g:50 mL, the mixed acid is a mixture of sulfuric acid and nitric acid, the volume ratio is 1:0.5, the mass concentration of sulfuric acid is 70%, and the mass concentration of nitric acid is 65%, react at 90°C for 0.5h, filter and wash, and dry at 110°C for 10h to obtain acidified carbon nanotubes; A2. Mix the acid-treated carbon nanotubes with nano-alumina, add ethanol and mix evenly, the mass of ethanol is 5% of the total mass of the acid-treated carbon nanotubes and nano-alumina, dry at 110°C for 1 hour, and heat at 800°C for 1 hour to obtain modified carbon nanotubes.
[0036] Comparative Example 3 The difference between this comparative example and Example 2 is that the raw materials for modifying carbon nanotubes in this comparative example include the following components by weight: 3 parts of nano magnesium oxide and 50 parts of carbon nanotubes; The method for preparing modified carbon nanotubes comprises the following steps: A1. Place carbon nanotubes in mixed acid, the mass volume ratio of carbon nanotubes to mixed acid is 1 g:50 mL, the mixed acid is a mixture of sulfuric acid and nitric acid, the volume ratio is 1:0.5, the mass concentration of sulfuric acid is 70%, and the mass concentration of nitric acid is 65%, react at 90°C for 0.5h, filter and wash, and dry at 110°C for 10h to obtain acidified carbon nanotubes; A2. Mix the acid-treated carbon nanotubes with nano-magnesium oxide, add ethanol and mix evenly, the mass of ethanol is 5% of the total mass of the acid-treated carbon nanotubes and nano-magnesium oxide, dry at 110°C for 1 hour, and heat at 800°C for 1 hour to obtain modified carbon nanotubes.
[0037] Comparative Example 4 The difference between this comparative example and Example 2 is that the raw materials of this comparative example do not include molybdenum disulfide and the weight portion of low-carbon ferromanganese is 6 parts.
[0038] Comparative Example 5 The difference between this comparative example and Example 2 is that the raw materials of this comparative example do not include low-carbon ferromanganese, and the weight portion of molybdenum disulfide is 6 parts.
[0039] Test example According to GB / T 18301-2012 Test Method for Abrasion Resistance of Refractory Materials at Room Temperature, the wear-resistant refractory bricks prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were cut into samples with a size of 100 mm × 100 mm × 25 mm, and the wear resistance at room temperature was measured. The wear amount A was calculated by the volume change method. The test results of each embodiment and comparative example are shown in Table 1.
[0040] Table 1 Test results of wear resistance at room temperature
[0041] By comparing Example 2 with Comparative Examples 1 to 3, it can be seen that the use of nano-alumina and nano-magnesium oxide to modify carbon nanotubes reduces the amount of wear and improves the wear resistance of wear-resistant refractory bricks. By comparing Example 2 with Comparative Examples 4 to 5, it can be seen that molybdenum disulfide and low-carbon ferromanganese work synergistically to reduce the amount of wear and improve the wear resistance of wear-resistant refractory bricks. By comparing Examples 5 to 7 with Comparative Examples 3 to 4, it can be seen that when the mass ratio of molybdenum disulfide to low-carbon ferromanganese is 1 to 3:1, the amount of wear can be further reduced and the wear resistance of wear-resistant refractory bricks can be further improved. By comparing Example 6 with Examples 5 and 7, it can be seen that the mass ratio of molybdenum disulfide to low-carbon ferromanganese is 2:1, which is the optimal ratio, which can further reduce the amount of wear and further improve the wear resistance of wear-resistant refractory bricks.
[0042] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A wear-resistant refractory brick, characterized in that: The raw materials include the following components by weight: 5-10 parts of graphene, 5-10 parts of silicon carbide, 5-15 parts of mullite, 15-30 parts of high-alumina bauxite, 5-10 parts of aluminum powder, 5-12 parts of molybdenum disulfide, 1-10 parts of low-carbon ferromanganese, and 5-10 parts of modified carbon nanotubes; The raw materials for modifying the carbon nanotubes include the following components by weight: 1 to 3 parts of nano-aluminum oxide, 2 parts of nano-magnesium oxide and 50 parts of carbon nanotubes.
2. A wear-resistant refractory brick according to claim 1, characterized in that: The mass ratio of the molybdenum disulfide to the low-carbon ferromanganese is 1-3:
1.
3. A wear-resistant refractory brick according to claim 2, characterized in that: The mass ratio of the molybdenum disulfide to the low-carbon ferromanganese is 2:
1.
4. A wear-resistant refractory brick according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: A1, placing carbon nanotubes in acid, reacting, filtering, washing, and drying to obtain acid-treated carbon nanotubes; A2, mixing the acid-treated carbon nanotubes with nano-alumina and nano-magnesia, adding ethanol to mix evenly, drying, and modifying to obtain the modified carbon nanotubes.
5. A wear-resistant refractory brick according to claim 4, characterized in that: The mass volume ratio of the carbon nanotubes to the acid is 1g:50-150mL.
6. A wear-resistant refractory brick according to claim 4, characterized in that: The acid described in A1 is a mixture of sulfuric acid and nitric acid.
7. A wear-resistant refractory brick according to claim 6, characterized in that: The volume ratio of the sulfuric acid to the nitric acid is 1:0.5-1.5, the mass concentration of the sulfuric acid is 70%-98%, and the mass concentration of the nitric acid is 65%-80%.
8. A method for preparing a wear-resistant refractory brick according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing and calcining graphene, silicon carbide and mullite to obtain a first mixed material; S2, mixing the first mixture with high-alumina bauxite, aluminum powder, molybdenum disulfide, low-carbon ferromanganese, and modified carbon nanotubes to obtain a second mixture, and the second mixture is pressure-formed to obtain a brick; S3. After being dried, fired and kept warm, the bricks are cooled to room temperature to obtain wear-resistant refractory bricks.
9. The method for preparing a wear-resistant refractory brick according to claim 8, characterized in that: The sintering described in S3 includes three stages. In the first stage, the temperature is heated from room temperature to 400~600℃, and the insulation time is 2~4h; in the second stage, the temperature is continuously heated to 1000~1200℃, and the insulation time is 2~4h; in the third stage, the temperature is continuously heated to 1500~1700℃, and the insulation time is 8~10h.
10. The method for preparing a wear-resistant refractory brick according to claim 8, characterized in that: The insulation in S3 includes two stages. In the first stage, the temperature is 250-300°C and the insulation time is 2-4 hours. In the second stage, the temperature is lowered to 100-130°C and the insulation time is 2-4 hours.